Pleomorphic malignant fibrous histiocytoma/undifferentiated pleomorphic sarcoma of the glans penis - Seo, Ill Young (Canadian Medical Association, 2013)
Primary sarcoma of the penis has an extremely low incidence, and its diagnosis and treatment are unclear. A 55-year-old man presented with an oval-shaped mass of the glans penis, which was treated by a wide excision. The pathologic result revealed an undifferentiated high-grade sarcoma, which was diagnosed as a pleomorphic malignant fibrous histiocytoma/undifferentiated pleomorphic sarcoma based on the World Health Organization classification. There was no recurrence at the12-months postoperative follow-up.